THE RISE OF DEFERENCE: THE MARGIN OF APPRECIATION AND DECENTRALIZED JUDICIAL REVIEW IN EU FREE MOVEMENT LAW - Zglinski, J (Kluwer Law International, 2018)
An institution erstwhile known for its activism, the ECJ has, in recent years, rendered a growing number of judgments marked by caution, especially when reviewing Member State acts. Through doctrines such as the margin of appreciation, the Court has granted national authorities substantial deference. This article investigates how and when the Court defers to the Member States. It focuses on free movement adjudication and, more specifically, on the way in which the ECJ conducts justification and proportionality review. Drawing on an empirical study of free movement case law (1974-2013), it is argued that an important shift has taken place in EU law: the ECJ is scaling down its control over Member State measures and increasingly delegates decision-making tasks to national institutions, both political and judicial.